Extrusion of high moisture PHA
By mixing and extruding the polyhydroxy fatty acid ester with a high moisture content with resin additives at high temperatures, the hydrolysis and degradation problem of the polyhydroxy fatty acid ester when extruded under high humidity conditions is solved, and an efficient extrusion process is achieved and the molecular weight is retained.
Patent Information
- Application Number
- CN202380068138.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-03
- Filing Date
- 2023-10-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-02
AI Technical Summary
When polyhydroxy fatty acid esters are extruded under high humidity conditions, the prior art requires the reduction of moisture content through drying to avoid hydrolysis and degradation, and the drying process consumes high energy and takes a long time.
At a temperature of about 120°C to about 190°C, a polyhydroxy fatty acid ester powder with a high moisture content is mixed with a resin additive to form an extrusion mixture and extruded through an extrusion die to form a resin extrusion.
Extrusion of polyhydroxy fatty acid ester with high moisture content without long drying is achieved, significant polymer degradation is avoided, and more than 80% of the initial molecular weight is retained.
Smart Images

Figure BDA0005323639780000071
Abstract
Description
Technical Field
[0001] The present disclosure relates to biodegradable polymer compositions. More particularly, the present disclosure relates to biodegradable polymers, such as polyhydroxyalkanoates, extruded under high humidity conditions. Background Art
[0002] Many polymeric materials, including biodegradable polymers such as polyhydroxyalkanoates, are often extruded to form a final product or intermediate pellets that will subsequently be remelted and formed into a final product.
[0003] Generally, it is necessary to thoroughly dry the polymer before heating and extruding it. This process is particularly true for polyhydroxyalkanoates. Generally, if the polyhydroxyalkanoate is not dried to a very low moisture content before heating and extruding, significant degradation of the polyhydroxyalkanoate due to hydrolysis (with a concomitant decrease in molecular weight) is observed.
[0004] However, such drying of polyhydroxyalkanoates is an energy and time intensive process. Therefore, it is desirable to melt extrude polyhydroxyalkanoates having a higher initial moisture content, thereby reducing the need for a lengthy drying process prior to melt extrusion. At the same time, the polyhydroxyalkanoates should not exhibit significant hydrolytic degradation or molecular weight loss of the polymer. Summary of the invention
[0005] According to the present disclosure, the above and other needs are met by a method of extruding high moisture polyhydroxyalkanoates. In one embodiment, the method of the present disclosure includes the steps of mixing at least one polyhydroxyalkanoate in powder form with at least one resin additive at a temperature of about 120°C to about 190°C to form an extrusion mixture. The mixture is then extruded through an extrusion die to form a resin extrudate comprising at least one polyhydroxyalkanoate and at least one resin additive.
[0006] According to the present disclosure, when mixed with at least one resin additive, at least one polyhydroxyalkanoate in powder form has an initial (i.e., before mixing) moisture content of at least 0.10 wt % as determined according to ASTM D7191-05. In certain embodiments, the polyhydroxyalkanoate powder has an even higher moisture content. In some cases, when mixed with at least one resin additive, at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 1 wt %, at least 5 wt %, at least 10 wt %, at least 15 wt %, or even higher as determined according to ASTM D7191-05.
[0007] According to certain embodiments, the mixing step and the extruding step are preferably carried out in different devices or different chambers of the same device. In some cases, the mixing step is preferably carried out in a low shear continuous mixer. In some embodiments, the extruding step is preferably carried out in a screw extruder.
[0008] In some cases, it is preferred that the at least one polyhydroxyalkanoate has an initial weight average molecular weight before the mixing step and a final weight average molecular weight after the extrusion step, wherein the final weight average molecular weight is at least 40% of the initial weight average molecular weight, wherein all weight average molecular weights are determined according to ASTM D5296-05. More preferably, the final weight average molecular weight of the at least one polyhydroxyalkanoate is at least 70% of the initial weight average molecular weight, more preferably at least 80% of the initial weight average molecular weight, and even more preferably at least 85% of the initial weight average molecular weight.
[0009] A variety of different forms of polyhydroxyalkanoates can be used in the methods of the present disclosure. In certain embodiments, at least one polyhydroxyalkanoate is made from poly(3-hydroxybutyrate-3-hydroxyhexanoate) ("P(3HB-co-3HHx)"). In some embodiments, P(3HB-co-3HHx) is preferably made from about 75 to about 99 mole % of hydroxybutyrate and about 1 to about 25 mole % of hydroxyhexanoate.
[0010] In other embodiments, preferably, at least one polyhydroxyalkanoate is made from about 1 to about 25 weight percent of at least one polyhydroxyalkanoate, comprising about 25 to about 50 mole percent of hydroxyvalerate, hydroxyhexanoate, hydroxyoctanoate and / or hydroxydecanoate. In some embodiments, preferably, at least one polyhydroxyalkanoate comprises a terpolymer made from about 75 to about 99.9 mole percent of 3-hydroxybutyrate monomer residues, about 0.1 to about 25 mole percent of 3-hydroxyhexanoate monomer residues, and about 0.1 to about 25 mole percent of a third 3-hydroxyalkanoate monomer residue having 5 to 12 carbon atoms.
[0011] In some cases, it is preferred that the at least one polyhydroxyalkanoate has an initial weight average molecular weight of about 50,000 Daltons to about 2.5 million Daltons as determined according to ASTM D5296-05.
[0012] According to certain embodiments, preferably, the at least one resin additive comprises at least one rheology modifier selected from the group consisting of vinyl acetate homopolymers or copolymers, peroxides, epoxides, isocyanates, carbodiimides, and mixtures thereof.
[0013] In some embodiments, preferably, the at least one resin additive comprises at least one nucleating agent selected from the group consisting of pentaerythritol, boron nitride, polyhydroxybutyrate, inositol, clay, dipentaerythritol, sorbitol, and mixtures thereof.
[0014] In some cases, it is preferred that the at least one resin additive comprises at least one filler selected from the group consisting of aragonite, clay, calcium carbonate, cellulose, nanocellulose, talc, kaolin, montmorillonite, bentonite, silica, chitin, starch, diatomaceous earth, titanium dioxide, nanoclay, mica, and mixtures thereof.
[0015] In addition, in certain embodiments, the mixing step may also include mixing at least one polyhydroxyalkanoate in powder form with at least one biopolymer selected from a biodegradable polymer, wherein the biodegradable polymer is selected from the group consisting of polybutylene succinate, polycaprolactone, polybutylene succinate-co-butylene adipate, polybutylene adipate-co-terephthalate, polylactic acid, cellulose acetate, and mixtures thereof. DETAILED DESCRIPTION
[0016] The present disclosure provides a method for extruding high moisture polyhydroxyalkanoates. Typically, polyhydroxyalkanoates must be dried to very low moisture content before extrusion to prevent hydrolytic degradation of the polyhydroxyalkanoates.
[0017] However, according to the methods of the present disclosure, the inventors have discovered that polyhydroxyalkanoates having significantly higher moisture contents can be extruded without significant polymer degradation due to hydrolysis.
[0018] Generally speaking, the method of the present disclosure includes a first step of mixing at least one polyhydroxyalkanoate in powder form with at least one resin additive to form an extrusion mixture at a temperature of about 120° C. to about 190° C. The mixture is then extruded through an extrusion die to form a resin extrudate comprising at least one polyhydroxyalkanoate and at least one resin additive.
[0019] As mentioned above, before the mixing step, at least one polyhydroxyalkanoate in powder form has an abnormally high initial moisture content. Generally, when mixed with at least one resin additive, at least one polyhydroxyalkanoate has an initial (pre-mixing) moisture content of at least 0.1 wt %, measured according to ASTM D7191-05. In some cases, the polyhydroxyalkanoate powder has an even higher moisture content. For example, when mixed with at least one resin additive, at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 1 wt %, at least 5 wt %, at least 10 wt %, or even at least 15 wt %, measured according to ASTM D7191-05.
[0020] The methods of the present disclosure can be practiced using various forms of polyhydroxyalkanoates, including homopolymers, copolymers, terpolymers, and mixtures of the foregoing.
[0021] Thus, in some embodiments, the polyhydroxyalkanoate includes a homopolymer, such as polyhydroxybutyrate.
[0022] In other cases, the polyhydroxyalkanoate comprises a copolymer or a terpolymer. For example, in some embodiments, at least one polyhydroxyalkanoate comprises poly(3-hydroxybutyrate-3-hydroxyhexanoate) ("P(3HB-co-3HHx)"). In some embodiments, the P(3HB-co-3HHx) is preferably made of about 75 to about 99 mole % hydroxybutyrate and about 1 to about 25 mole % hydroxyhexanoate.
[0023] In other embodiments, preferably, at least one polyhydroxyalkanoate comprises about 1 to about 25 weight percent of at least one polyhydroxyalkanoate comprising about 25 to about 50 mole percent of hydroxyvalerate, hydroxyhexanoate, hydroxyoctanoate and / or hydroxydecanoate. In other embodiments, preferably, at least one polyhydroxyalkanoate comprises a terpolymer made from about 75 to about 99.9 mole percent of 3-hydroxybutyrate monomer residues, about 0.1 to about 25 mole percent of 3-hydroxyhexanoate monomer residues, and about 0.1 to about 25 mole percent of a third 3-hydroxyalkanoate monomer residue having 5 to 12 carbon atoms.
[0024] At least one resin additive is mixed with the polyhydroxyalkanoate to form an extrusion mixture. Examples of resin additives mixed with the polyhydroxyalkanoate include rheology modifiers, nucleating agents, organic fillers, inorganic fillers, polyesters, and impact modifiers.
[0025] For example, in certain embodiments, it is preferred that the at least one resin additive comprises at least one rheology modifier selected from the group consisting of vinyl acetate homopolymers or copolymers, peroxides, epoxides, isocyanates, carbodiimides, and mixtures thereof.
[0026] In some embodiments, preferably, the at least one resin additive comprises at least one nucleating agent selected from the group consisting of pentaerythritol, boron nitride, polyhydroxybutyrate, inositol, clay, dipentaerythritol, sorbitol, and mixtures thereof.
[0027] In some cases, it is preferred that the at least one resin additive comprises at least one filler selected from the group consisting of aragonite, clay, calcium carbonate, cellulose, nanocellulose, talc, kaolin, montmorillonite, bentonite, silica, chitin, starch, diatomaceous earth, titanium dioxide, nanoclay, mica, and mixtures thereof.
[0028] In addition, in certain embodiments, the mixing step further comprises mixing at least one polyhydroxyalkanoate in powder form with at least one biopolymer selected from a biodegradable polymer selected from the group consisting of polybutylene succinate, polycaprolactone, polybutylene succinate-adipate, polybutylene adipate-terephthalate, polylactic acid, cellulose acetate, and mixtures thereof. In these embodiments, the additional biopolymer may be added to the mixture in a weight ratio of about 1 to about 75 parts by weight of the biopolymer per 100 parts by weight of the at least one polyhydroxyalkanoate.
[0029] According to the present disclosure, the mixing step and the extrusion step are performed separately. In some cases, the mixing step and the extrusion step are performed in different devices. In other cases, the mixing step and the extrusion step are performed in different chambers of a single device.
[0030] For example, according to certain embodiments of the present disclosure, the mixing step is preferably performed in a continuous mixer, typically operating under relatively low shear mixing conditions. One example of a suitable mixing system is the Farrel continuous mixer, available from Farrel Pomini Corporation.
[0031] Generally speaking, continuous mixers (such as the Farrel mixer described above) have a mixing chamber having two counter-rotating non-meshing rotors (i.e., screws) for mixing materials. As described above, the threads of the two rotors do not mesh with each other, and the rotors are sized to provide a relatively large free volume in the mixing chamber. This larger free volume in the mixing chamber is due to the lack of intermeshing of the rotor threads and the relatively large gap between the screw threads and the wall of the extrusion chamber. In conventional screw extruders, this gap is quite small, and when the material passes through this tight gap, it will exert great shear forces on the material. Because the gap in the continuous mixer is larger, the shear force exerted on the material when the material passes through the gap is reduced. This lower shear force is believed to reduce the amount of degradation of the material.
[0032] Furthermore, the continuous mixer also allows for internal water cooling of the extruder screw.Preferably, the extruder screw is cooled to maintain the material in the mixer at a temperature of about 120°C to about 190°C.
[0033] After initial mixing under the above conditions, the extrusion mixer can then be transferred to a conventional screw extruder for the final extrusion step.
[0034] As noted above, it was unexpectedly observed that despite the elevated moisture content of the starting polyhydroxyalkanoate, the polyhydroxyalkanoates compounded and extruded according to the present disclosure did not exhibit a significant degree of polymer degradation due to hydrolysis.
[0035] For example, in some cases, preferably, at least one polyhydroxyalkanoate has an initial (i.e., before mixing with the resin additive) weight average molecular weight of about 50,000 Daltons to about 2.5 million Daltons as determined according to ASTM D5296-05. More preferably, at least one polyhydroxyalkanoate preferably has an initial weight average molecular weight of about 300,000 Daltons to about 2.5 million Daltons as determined according to ASTM D5296-05.
[0036] Advantageously, according to the present disclosure, preferably, at least one polyhydroxyalkanoate has an initial weight average molecular weight before the mixing step and a final weight average molecular weight after the extrusion step, the final weight average molecular weight being at least 40% of the initial weight average molecular weight, wherein all weight average molecular weights are determined according to ASTM D5296-05. More preferably, the final weight average molecular weight of the at least one polyhydroxyalkanoate is at least 70% of the initial weight average molecular weight, more preferably at least 80% of the initial weight average molecular weight, and even more preferably at least 85% of the initial weight average molecular weight.
[0037] Example
[0038] The following non-limiting examples illustrate various additional aspects of the invention. Unless otherwise indicated, temperatures are in degrees Celsius and percentages are by weight based on the dry weight of the formulation.
[0039] Examples 1-24
[0040] For these embodiments, according to the present disclosure, a series of polyhydroxyalkanoate (PHA) samples were prepared, each sample having a different initial moisture content of 0.15 wt % to about 15 wt %. For each sample, the PHA was a poly (3-hydroxybutyrate-3-hydroxyhexanoate) copolymer, comprising about 6 mol % of 3-hydroxyhexanoate monomer repeating units. The initial weight average molecular weight of the PHA copolymer was about 1,032,000 as determined according to ASTM D5296.
[0041] PHA is initially provided in the form of a substantially dry powder. For each sample, the powder is mixed with a known amount of water in a bucket and stirred with a paint shaker to provide a PHA sample with a known initial moisture content.
[0042] Each sample of PHA was then mixed using a Farrel C-PEX lab scale continuous mixer. The PHA material was fed through the continuous mixer at a rate of about 12 kg / hour. For convenience, in these examples, PHA was mixed alone in the continuous mixer without any additives. The temperature profile within the continuous mixer was set to 140°C. In addition, the mixing screw within the continuous mixer was internally cooled using cooling water.
[0043] After feeding through the continuous mixer, the material falls into the conveying screw which pumps the material steadily to the extrusion die to allow extrusion and pelletization. The conveying screw is a single screw extruder set in the temperature range of 120-140°C.
[0044] After extrusion and pelletization, the pellets of each PHA sample were tested to determine the final weight average molecular weight (Mw) of the PHA and the final melt flow index (MFR) of the PHA. The molecular weight was determined by gel permeation chromatography according to ASTM D5296. The melt flow index was determined at 175°C and 10 kg load according to ASTM D1238. The results are reported in Table 1 below:
[0045] Table 1
[0046] Example Initial water content (wt%) Final MFR (g / 10min) Final Mw (g / mol) Mw reduction % 1 0.15 4.7 848,946 17.74 2 0.19 4.6 802,536 22.23 3 0.23 4.51 879,750 14.75 4 0.23 6.11 811,246 21.39 5 0.4 4.56 827,916 19.78 6 0.41 5.3 862,950 16.38 7 0.65 4.77 890,776 13.68 8 0.68 5.1 837,293 18.87 9 0.89 5.61 848,470 17.78 10 0.93 5.08 839,212 18.68 11 0.97 5.05 865,231 16.16 12 1.24 4.87 906,173 12.19 13 1.6 4.38 961,481 6.83 14 2.47 4.6 877,781 14.94 15 2.53 4.88 793,130 23.15 16 3.1 4.4 875,546 15.16 17 3.27 4.9 864,512 16.23 18 3.72 5.4 824,430 20.11 19 5.76 4.33 847,274 17.90 20 6.23 4.46 863,577 16.32 21 6.64 4.63 797,797 22.69 22 8.37 4.6 815,008 21.03 23 8.56 4.65 824,207 20.13 24 9.11 4.8 832,601 19.32 25 9.11 5.9 863,808 16.30 26 9.38 4.76 902,910 12.51 27 10.02 4.52 865,384 16.14 28 10.27 4.72 901,443 12.65 29 10.29 7.1 917,349 11.11 30 12.12 6.37 887,559 14.00 31 14.08 5.33 897,974 12.99 32 14.5 5.6 892,237 13.54 33 14.85 5.71 884,850 14.26 34 15.04 5.11 904,070 12.40
[0047] It can be seen that when PHA is first processed in a continuous mixer according to the present disclosure and then extruded, in almost all cases, the PHA retains at least 80% of its initial weight average molecular weight. In many cases, the PHA retains at least 85% of its initial weight average molecular weight. In addition, the final melt flow index of the PHA is less than 6.0 in almost all cases, and less than 5.0 g / 10 min in many cases. Since the melt flow index generally increases with decreasing molecular weight, these melt flow index values also indicate that the degradation of the PHA and the decrease in weight average molecular weight are relatively small.
[0048] These results are quite surprising considering the large initial moisture content in the PHA samples before processing in the continuous mixer and subsequent extrusion.
[0049] As mentioned above, in the foregoing examples, no additives were mixed with the PHA. However, one skilled in the art will appreciate that the inclusion or absence of additives (e.g., rheology modifiers, nucleating agents, organic fillers, inorganic fillers, polyesters, and impact modifiers) will not affect the molecular weight of the PHA. Therefore, after mixing and extrusion, the molecular weight values of the PHA are similar with or without further resin additives.
[0050] Comparative Examples 35-38
[0051] For comparison, another series of PHA samples were prepared. As with the previous samples, the PHA is a poly (3-hydroxybutyrate-3-hydroxyhexanoate) copolymer containing about 6 mol% of 3-hydroxyhexanoate monomer repeating units. The initial weight average molecular weight of the PHA copolymer is about 600,000 to about 1,100,00 g / mol, as shown in the following table.
[0052] As with the previous samples, the PHA was initially provided in a substantially dry powder form. For each sample, the powder was mixed with a known amount of water in a bucket and stirred with a paint shaker to provide a PHA sample with a known initial moisture content.
[0053] Unlike the previous samples, these control samples were prepared using an Entek 27 mm twin screw laboratory scale extruder for comparative purposes. In the extruder, the PHA was heated to a temperature of about 120-140°C and then extruded through a double hole die into a water bath set at 150°F to 160°F (65°C to 71°C). The extruded PHA was then cut into pellets.
[0054] As in the previous examples, after extrusion and pelletization, the pellets of each PHA sample were tested to determine the final weight average molecular weight of the PHA and the final melt flow index of the PHA. Molecular weight was determined by gel permeation chromatography according to ASTM D5296. Melt flow index was determined at 175°C and 10 kg load according to ASTM D1238. The results are reported in Table 2 below.
[0055] Table 2
[0056]
[0057] These results are in stark contrast to the results described above using a continuous mixer. In four of the five comparative examples, molecular weight losses of over 35% were observed when starting with PHAs having an initial moisture content of only 0.10-0.15 wt %. Again, for the previous examples, significantly lower losses in weight average molecular weight were observed in accordance with the present disclosure, even though the initial moisture content of the PHAs was more than an order of magnitude higher than the comparative examples.
[0058] Furthermore, it was observed that the melt flow index of the comparative example was also significantly higher than that of the previous example using a continuous mixer.
[0059] The following embodiments further illustrate the present disclosure:
[0060] Embodiment 1. A method of extruding a resin comprising a polyhydroxyalkanoate, the method comprising the steps of:
[0061] mixing at least one polyhydroxyalkanoate in powder form with at least one resin additive at a temperature of about 120° C. to about 190° C. to form an extrusion mixture; and
[0062] extruding the mixture through an extrusion die to form a resin extrudate comprising at least one polyhydroxyalkanoate and at least one resin additive,
[0063] Wherein the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 0.10 wt % when mixed with the at least one resin additive as measured according to ASTM D7191-05.
[0064] Embodiment 2. The method according to embodiment 1, wherein when mixed with the at least one resin additive, the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 1% by weight as measured according to ASTM D7191-05.
[0065] Embodiment 3. A method according to embodiment 1 or 2, wherein when mixed with the at least one resin additive, the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least wt.%, more preferably at least 10 wt.%, and even more preferably at least 15 wt.%, as measured according to ASTM D7191-05.
[0066] Embodiment 4. The method according to any of the preceding embodiments, wherein the mixing step and the extrusion step are performed in different devices or in different chambers of the same device.
[0067] Embodiment 5. The method according to any of the preceding embodiments, wherein the mixing step is performed in a continuous mixer.
[0068] Embodiment 6. The method according to any of the preceding embodiments, wherein the extrusion step is performed in a screw extruder.
[0069] Embodiment 7. A method according to any of the preceding embodiments, wherein the at least one polyhydroxyalkanoate has an initial weight average molecular weight before the mixing step and a final weight average molecular weight after the extrusion step, and the final weight average molecular weight is at least 40%, at least 70%, at least 80%, or at least 85% of the initial weight average molecular weight, wherein all weight average molecular weights are determined according to ASTM D5296-05.
[0070] Embodiment 8. The method according to any of the preceding embodiments, wherein the at least one polyhydroxyalkanoate comprises poly(3-hydroxybutyrate-3-hydroxyhexanoate) ("P(3HB-co-3HHx)").
[0071] Embodiment 9. The method of embodiment 8, wherein P(3HB-co-3HHx) comprises about 75 to about 99 mol % hydroxybutyrate and about 1 to about 25 mol % hydroxyhexanoate.
[0072] Embodiment 10. A method according to any of the preceding embodiments, wherein the at least one polyhydroxyalkanoate comprises from about 1 to about 25 weight percent of at least one polyhydroxyalkanoate, the polyhydroxyalkanoate comprising from about 25 to about 50 mole percent of hydroxyvalerate, hydroxyhexanoate, hydroxyoctanoate and / or hydroxydecanoate.
[0073] Embodiment 11. A method according to any of the preceding embodiments, wherein the at least one polyhydroxyalkanoate comprises a terpolymer made from about 75 to about 99.9 mole % of 3-hydroxybutyrate monomer residues, about 0.1 to about 25 mole % of 3-hydroxyhexanoate monomer residues, and about 0.1 to about 25 mole % of a third 3-hydroxyalkanoate monomer residue having 5 to 12 carbon atoms.
[0074] Embodiment 12. The method according to any of the preceding embodiments, wherein the at least one polyhydroxyalkanoate has an initial weight average molecular weight of about 50,000 Daltons to about 2.5 million Daltons as determined according to ASTM D5296-05.
[0075] Embodiment 13. The method according to any of the preceding embodiments, wherein the at least one resin additive comprises at least one rheology modifier selected from the group consisting of vinyl acetate homopolymers or copolymers, peroxides, epoxides, isocyanates, carbodiimides, and mixtures thereof.
[0076] Embodiment 14. The method according to any of the preceding embodiments, wherein the at least one resin additive comprises at least one nucleating agent selected from the group consisting of pentaerythritol, boron nitride, polyhydroxybutyrate, inositol, clay, dipentaerythritol, sorbitol, and mixtures thereof.
[0077] Embodiment 15. The method according to any of the preceding embodiments, wherein the at least one resin additive comprises at least one filler selected from the group consisting of aragonite, clay, calcium carbonate, cellulose, nanocellulose, talc, kaolin, montmorillonite, bentonite, silica, chitin, starch, diatomaceous earth, titanium dioxide, nanoclay, mica, and mixtures thereof.
[0078] Embodiment 16. A method according to any of the preceding embodiments, wherein the mixing step further comprises mixing the at least one polyhydroxyalkanoate in powder form with at least one biopolymer selected from biodegradable polymers, wherein the biodegradable polymer is selected from the group consisting of polybutylene succinate, polycaprolactone, polybutylene succinate-adipate, polybutylene adipate-terephthalate, polylactic acid, cellulose acetate, and mixtures thereof.
[0079] The foregoing description of the preferred embodiments of the present invention is intended to illustrate and describe. They are not intended to be exhaustive or to limit the present invention to the precise form disclosed. In light of the above teachings, obvious modifications or variations are possible. The embodiments are selected and described in order to provide the best illustration of the principles of the present invention and its practical application, so that those of ordinary skill in the art can utilize the present invention in various embodiments and make various modifications to suit the specific purposes envisioned. All such modifications and variations are within the scope of the present invention as determined by the appended claims when interpreted in accordance with the scope of fair, legal and equitable authorization.
Claims
1. A method for extruding a resin comprising a polyhydroxyalkanoate, the method comprising the steps of: mixing at least one polyhydroxyalkanoate in powder form with at least one resin additive at a temperature of 120° C. to 190° C. to form an extrusion mixture; and extruding the mixture through an extrusion die to form a resin extrudate comprising the at least one polyhydroxyalkanoate and the at least one resin additive, Wherein when mixed with at least one resin additive, the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 0.1 wt % as measured according to ASTM D7191-05.
2. The method of claim 1, wherein the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 1 wt. % when mixed with the at least one resin additive, as determined according to ASTM D7191-05.
3. The method of claim 1, wherein the at least one polyhydroxyalkanoate in powder form has an initial moisture content of at least 5 wt. % when mixed with the at least one resin additive as determined according to ASTM D7191-05.
4. The method of claim 1, wherein the mixing step and the extruding step are performed in different devices or in different chambers of the same device.
5. The method of claim 1, wherein the mixing step is performed in a continuous mixer.
6. The method of claim 1, wherein the extruding step is performed in a screw extruder.
7. The method of claim 1, wherein the at least one polyhydroxyalkanoate has an initial weight average molecular weight prior to the mixing step and a final weight average molecular weight after the extruding step, wherein the final weight average molecular weight is at least 40% of the initial weight average molecular weight, wherein all weight average molecular weights are determined according to ASTM D5296-05.
8. The method of claim 1, wherein the at least one polyhydroxyalkanoate comprises poly(3-hydroxybutyrate-3-hydroxyhexanoate) ("P(3HB-co-3HHx)").
9. The method of claim 8, wherein the P(3HB-co-3HHx) comprises 75 to 99 mol% of hydroxybutyrate and 1 to 25 mol% of hydroxyhexanoate.
10. The method of claim 1, wherein the at least one polyhydroxyalkanoate comprises 1 wt% to 25 wt% of at least one polyhydroxyalkanoate comprising 25 mol% to 50 mol% of hydroxyvalerate, hydroxyhexanoate, hydroxyoctanoate and / or hydroxydecanoate.
11. The method of claim 1 , wherein the at least one polyhydroxyalkanoate comprises a terpolymer made from 75 to 99.9 mole % of 3-hydroxybutyrate monomer residues, 0.1 to 25 mole % of 3-hydroxyhexanoate monomer residues, and 0.1 to 25 mole % of a third 3-hydroxyalkanoate monomer residue having 5 to 12 carbon atoms.
12. The method of claim 1, wherein the at least one polyhydroxyalkanoate has an initial weight average molecular weight of 50,000 Daltons to 2.5 million Daltons as determined according to ASTM D5296-05.
13. The method of claim 1, wherein the at least one resin additive comprises at least one rheology modifier selected from the group consisting of vinyl acetate homopolymers or copolymers, peroxides, epoxides, isocyanates, carbodiimides, and mixtures thereof.
14. The method of claim 1, wherein the at least one resin additive comprises at least one nucleating agent selected from the group consisting of pentaerythritol, boron nitride, polyhydroxybutyrate, inositol, clay, dipentaerythritol, sorbitol, and mixtures thereof.
15. The method of claim 1, wherein the at least one resin additive comprises at least one filler selected from the group consisting of aragonite, clay, calcium carbonate, cellulose, nanocellulose, talc, kaolin, montmorillonite, bentonite, silica, chitin, starch, diatomaceous earth, titanium dioxide, nanoclay, mica, and mixtures thereof.
16. The method of claim 1, wherein the mixing step further comprises mixing the at least one polyhydroxyalkanoate in powder form with at least one biopolymer selected from the group consisting of biodegradable polymers selected from the group consisting of polybutylene succinate, polycaprolactone, polybutylene succinate-adipate, polybutylene adipate-terephthalate, polylactic acid, cellulose acetate, and mixtures thereof.
Citation Information
Patent Citations
Polyhydroxyalkanoate full-degradation composite material, preparation method and applications thereof
CN102850741A
Polymer composition
US20160060451A1
Method for producing moulded parts
US20170342261A1